1993
DOI: 10.4269/ajtmh.1993.48.700
|View full text |Cite
|
Sign up to set email alerts
|

High Human Malarial Infectivity to Laboratory-Bred Anopheles gambiae in a Village in Burkina Faso

Abstract: The malarial infectivity ofan African village population was tested by selecting a demographically representative sample of individuals for study, regardless of parasitemia or gametocytemia. The infectivity of this population people to laboratory-bred mosquitoes was investigated using membrane feeding techniques. Tests on 322 subjects (greater than

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 9 publications
4
62
2
1
Order By: Relevance
“…Studies are usually carried out by direct feeding or membrane feeding of laboratory-reared mosquitoes with blood from gametocyte carriers. Mosquitoes are examined later, at day 7 post infection, for oocyst detection (Draper 1953;Muirhead-Thomson 1957;Collins et al 1977;Boudin et al 1993;Tchuinkam et al 1993) or at day 12-14 for sporozoites (Collins et al1977;Boudin et al 1989). …”
Section: Introductionmentioning
confidence: 99%
“…Studies are usually carried out by direct feeding or membrane feeding of laboratory-reared mosquitoes with blood from gametocyte carriers. Mosquitoes are examined later, at day 7 post infection, for oocyst detection (Draper 1953;Muirhead-Thomson 1957;Collins et al 1977;Boudin et al 1993;Tchuinkam et al 1993) or at day 12-14 for sporozoites (Collins et al1977;Boudin et al 1989). …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Often, these studies were restricted to microscopically detected gametocyte carriers, even though it has been repeatedly shown that submicroscopic gametocyte densities may result in mosquito infection. 16,17 Although microscopically detectable gametocyte densities are more likely to result in mosquito infections compared with submicroscopic gametocyte densities, the contribution of submicroscopic gametocyte carriers to the total infectious reservoir may be considerable 18 and can only be determined in xenodiagnostic surveys where individuals are recruited for feeding experiments, regardless of their parasitemic status. A recent meta-analysis further suggests that direct skin feeding assays may be the most sensitive approach to determine human infectiousness to mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…Parasite species spend the majority of their lifecycles within the human host and, thus, have greater opportunity to interact within humans than within mosquitoes. However, as clearly parameterized in the classic Ross-Macdonald model of malaria [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Box 1), the distribution of vector-borne parasites depends on vector-vertebrate and vectorparasite interactions, in addition to interactions within vertebrates. Given that vector-based (as opposed to therapy-based) interventions represent the mainstay of prevention strategies, it seems essential to consider initially species differences that relate to vectorial parameters and, thus, the consequences of vector-based interventions for species distribution.…”
Section: Focus On Mixed-species Infectionsmentioning
confidence: 99%
“…c) remains unclear. Although transmission success generally increases with gametocyte density [21,22], there is considerable variation and a clear indication of age-dependent effects [23][24][25].…”
Section: Transmission Parameters B and Cmentioning
confidence: 99%